2022
DOI: 10.1111/jocd.15563
|View full text |Cite
|
Sign up to set email alerts
|

Clinical validation of the upper face first principle—A clinical, prospective, interventional split‐face study

Abstract: Background Previous clinical and anatomic investigations have identified the clinical relevance of facial biomechanics. Based on this new understanding, principles for facial aesthetic procedures were established: Lateral Face First, Deep Layers First, and Upper Face First. Objective To test the upper face first principle by showing that an injection sequence, starting in the upper face is superior to an injection sequence starting in the lower face. Methods This study was designed as an interventional split‐f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
(41 reference statements)
1
1
0
Order By: Relevance
“…This is in alignment with currently accepted treatment algorithms that predominantly target deep = supraperiosteal fascial layers to reshape and revolumize various facial regions including the midface. These observations are also in line with the previously established treatment principles for minimally invasive facial aesthetic procedures which were confirmed in independent clinical studies: lateral face first, upper face first, and deep layers first 1,5–7 …”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…This is in alignment with currently accepted treatment algorithms that predominantly target deep = supraperiosteal fascial layers to reshape and revolumize various facial regions including the midface. These observations are also in line with the previously established treatment principles for minimally invasive facial aesthetic procedures which were confirmed in independent clinical studies: lateral face first, upper face first, and deep layers first 1,5–7 …”
Section: Introductionsupporting
confidence: 88%
“…These observations are also in line with the previously established treatment principles for minimally invasive facial aesthetic procedures which were confirmed in independent clinical studies: lateral face first, upper face first, and deep layers first. 1,[5][6][7] Despite its global acceptance, the latter principle however (deep layers first) is being challenged by anatomic findings which investigated the superficial facial fat compartments individually and have reported that some superficial fat compartments move more (superficial nasolabial and jowl) whereas others are stable (superficial medial cheek and superficial lateral cheek) when experimentally tested and related to the underlying bone. Especially the superficial medial cheek fat compartment (which is also termed malar fat pad) seems to not undergo positional changes which might make this fat compartment also a target for superficial soft tissue filler injections in addition to the already established deep injections.…”
Section: Introductionmentioning
confidence: 99%